Correlación entre hallazgos de hábitos en higiene bucal y estado de salud oral en la población escolar de corpoadases (Corporación alianza para el desarrollo ambiental, social y económico sostenible). (2020)
Background: In the city of Bucaramanga there are sectors in a vulnerable situation, in which it is necessary to continuously evaluate the state of oral health and the habits and practices related to it. Objective: To know the oral hygiene habits and compare them with the bacterial plaque index and the presence of caries, in the school population of the Colombian Institute of Family Welfare ICBF, Corpoadases externado. Methodology: an exploratory descriptive observational study was carried out. The population consisted of 100 children, aged between 6 to 12 years. Clinical variables such as presence of caries, index of bacterial plaque and hygiene habits such as brushing, use of silk, rinsing, brushing frequency and perception in the consultation were evaluated according to a previously applied questionnaire. Informed parental consent and assent were requested. Exploratory analysis was performed in SPSS 25. Results: 68% of children are in primary school. 76% brush their teeth 2 or more times a day. More than 60% of children report having had a brush change in the last 3 months, however, more than 78% have a bad plaque index. In the bivariate analysis (plaque index / other variables) all showed a bad plaque index of more than 60% without significant differences. Regarding the bivariate (presence of dental caries / other variables), only the change of the brush showed significant differences (p = 0.05) in those who reported having changed the toothbrush in less than 3 months, since they did not present caries in 40 %. Conclusions: Deficiencies in the oral health status of children are observed in this population. and education is required at the household level.